Berliner Illustrirte Zeitung. (Berlin : Verlag Ullstein & Co, 1892)
The Berliner Illustrirte Zeitung (Berlin illustrated newspaper, or BIZ) was a weekly illustrated magazine published in Germany from 1882 to 1945 by the Berlin-based Ullstein Verlag. With a circulation of more than one million by 1920 and more than two million in the 1930s, BIZ grew to be the leading illustrated journal in Germany. With its sensational, eye-catching covers, the magazine placed photographic images at the center of its focus; in the interwar era its pages were filled with spectacular, sometimes humorous photographs documenting sports, leisure activities, political events, industrial innovations, arts, and entertainment. Widely acknowledged as a successful mass-market modern photography magazine, BIZ was a model for Henry Luce’s Life. A pioneer of the photoessay, BIZ published up-to-the-minute reportages of current events. It held an exclusive contract with Erich Salomon—whose behind-the-scenes snapshots (such as MoMA 1851.2001, featuring Marlene Dietrich) offered readers insider views of political meetings and celebrities’ lives—and frequently featured reportage by Felix H. Man (including MoMA 1776.2001, which was a cover image in August 1929). Keeping up with the period’s passion for aeronautics, BIZ featured spreads of record-setting transcontinental flights; aerial landscape photographs taken from a hot-air balloon (see MoMA 1811.2001); and daring feats, as in Willi Ruge’s spectacular photoessay I Photograph Myself during a Parachute Jump (Ich fotografiere mich beim Absturz mit dem Fallschirm), published May 24, 1931 (which included MoMA 1849.2001.11). Also popular were stop-action sports photographs (such as MoMA 1796.2001) by Martin Munkácsi, the magazine’s first staff photographer. In addition to contributions by its regular staff of photo-reporters, BIZ featured images by many of the leading photographers of the era, including Lotte Jacobi, Germaine Krull, Maurice Tabard, Umbo, André Kertész, Sasha Stone, Cami Stone, and Yva. Though BIZ remained nonpolitical
Online La Contemporaine: https://argonnaute.parisnanterre.fr/search?query=Berliner+Illustrirte+Zeitung&search-query=&search-query=1 (onvolledig)
Duits
Tijdschriften
Keywords: 20ste eeuw; Wereldoorlog I